2004
DOI: 10.1287/msom.1030.0034
|View full text |Cite
|
Sign up to set email alerts
|

How a Base Stock Policy Using "Stale" Forecasts Provides Supply Chain Benefits

Abstract: Managers often engage in forecast updating with the expectation that forecast updating reduces expected shortage and inventory costs. One undesirable effect of forecast updating is that it may lead to the bullwhip effect, a phenomenon where the variability of demand increases as one moves up the supply chain. The bullwhip effect can be undesirable for the supplier because more volatile orders from the downstream stage can be very costly to the supplier. It can make it more difficult for the supplier to forecas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The MMFE demand model described thus far generalizes many commonly used demand models in the literature, such as the i.i.d. normal demand model, the AR(1) model (Lee et al 2000, Raghunathan 2001), the IMA 0 1 1 model (Graves 1999, Miyaoka andHausman 2004), the general ARMA model (Gilbert 2005, Gaur et al 2005, the linear state-space model (Aviv 2003), and the advance demand information model (Gallego and Ozer 2001).…”
Section: A Generalized Demand Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The MMFE demand model described thus far generalizes many commonly used demand models in the literature, such as the i.i.d. normal demand model, the AR(1) model (Lee et al 2000, Raghunathan 2001), the IMA 0 1 1 model (Graves 1999, Miyaoka andHausman 2004), the general ARMA model (Gilbert 2005, Gaur et al 2005, the linear state-space model (Aviv 2003), and the advance demand information model (Gallego and Ozer 2001).…”
Section: A Generalized Demand Modelmentioning
confidence: 99%
“…Aviv (2003) used a general time-series framework to study the benefits of information sharing in supply chain management. Miyaoka and Hausman (2004) showed that under the IMA 0 1 1 demand model, using "stale" forecasts can reduce the bullwhip effect and improve fulfillment from the supplier to the retailer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have investigated possible ways to minimize the bullwhip effect. One approach has focused on the relative value of past demand information (Cachon, 1999;Miyaoka and Hausman, 2004;Balakrishnan et al, 2004;Daganzo, 2004); others focused on reducing lead time variability (Chatfield et al, 2004;Kim et al, 2006). Yet other authors have investigated the broader cost implications of the bullwhip effect (Metters, 1997;Chen and Samroengraja, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Zhang (2005) and Miyaoka and Hausman (2004) assume that the order-up-to level is updated every time period by using old forecast information and quantify the impact of such nonoptimum forecasting on a supply chain cost. In their model, however, the latest market demand information is exploited when the order quantity is determined.…”
Section: Introductionmentioning
confidence: 99%